In-vitro dissolution and some physical properties of two generics of levamisole blous formulations for large animals. (2017)
Physical and dissolution properties of solid oral dosage formulations significantly affect therapeutic outcomes following their use in veterinary medicine. Therapeutic failure of most levamisole boluses for the prevention and treatment of helminth infections have been a recurrent complaint from animal health workers and veterinarians in Nigeria. However, there is dearth of information on the quality of oral bolus formulations of levamisole for veterinary use in Nigeria. Consequently, the purpose of this study was to evaluate physical and dissolution properties of two generic products of levamisole boluses commonly used in large animal practice in Nigeria. Two frequently used generics of levamisole oral boluses for large animal practice (A & B) were evaluated for bolus weight uniformity, hardness, friability, disintegration and dissolution as specified in the United States Pharmacopoeia. The results demonstrated that generic B failed weight uniformity and friability tests, whereas generic A failed friability and disintegration tests. All the products passed dissolution profile test as specified. Consequently, the two products can be used interchangeably, however, generic B is recommended for treating acute enteric helminthosis because of its fast disintegration and dissolution rates as compared to generic A.